2022
DOI: 10.1093/nutrit/nuab105
|View full text |Cite
|
Sign up to set email alerts
|

Governing evidence use in the nutrition policy process: evidence and lessons from the 2020 Canada food guide

Abstract: Nutrition guideline development is traditionally seen as a mechanism by which evidence is used to inform policy decisions. However, applying evidence in policy is a decidedly complex and politically embedded process, with no single universally agreed-upon body of evidence on which to base decisions, and multiple social concerns to address. Rather than simply calling for “evidence-based policy,” an alternative is to look at the governing features of the evidence use system and reflect on what constitutes improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…In a study conducted by Weldon and Parkhurst that compared the 2019 CFG to the principles of good governance, it was found that the 2019 Food Guide's development process met 21 out of the 28 measurable indictors of good governance ( 33 ). To compare, the authors found that only 6 of the 28 indicators were met by the 2007 CFG ( 33 ). Overall, Weldon and Parkhurst concluded that legitimizing good governance like stewardship, transparency, and contestability through the institutionalization of evidentiary processes can help in maintaining public trust of CFG's healthy eating information, which may have significant ramifications for implementing and achieving dietary outcomes ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a study conducted by Weldon and Parkhurst that compared the 2019 CFG to the principles of good governance, it was found that the 2019 Food Guide's development process met 21 out of the 28 measurable indictors of good governance ( 33 ). To compare, the authors found that only 6 of the 28 indicators were met by the 2007 CFG ( 33 ). Overall, Weldon and Parkhurst concluded that legitimizing good governance like stewardship, transparency, and contestability through the institutionalization of evidentiary processes can help in maintaining public trust of CFG's healthy eating information, which may have significant ramifications for implementing and achieving dietary outcomes ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…To compare, the authors found that only 6 of the 28 indicators were met by the 2007 CFG ( 33 ). Overall, Weldon and Parkhurst concluded that legitimizing good governance like stewardship, transparency, and contestability through the institutionalization of evidentiary processes can help in maintaining public trust of CFG's healthy eating information, which may have significant ramifications for implementing and achieving dietary outcomes ( 33 ). To further understand the impact of Health Canada's revised evidence review process for dietary guidance, future research should explore the relationship between Canadians' trust and adherence and use of CFG's healthy eating guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations